إدارة مخاطر التمويل العقاري بالمصارف الإسلامية دراسة حالة بنك البركة الجزائري وكالة الوادي - هادية بدرالدين; حنان أحمودة; منال فريجات (university of eloued جامعة الوادي, 2025)
" تمحورت مذكرتنا حول تقييم مدى نجاعة إجراءات وأساليب إدارة مخاطر عقود التمويل العقاري في المصارف الإسلامية؛ من خلال التعرض إلى مختلف الصيغ التمويلية الموجهة للقطاع العقاري، والبنوك الإسلامية عرضة للمخاطر التي تهدد بقائها واستمرارها إذ تواجه نوعين من المخاطر؛ مخاطر تشترك فيها مع البنوك التقليدية كمخاطر الائتمان، السيولة والسوق...، أما الثانية مخاطر تتعلق بصيغ التمويل الإسلامية أهمها المخاطر الشرعية، وكذا مخاطر زيادة تكاليف حفظ وصيانة العقار؛ ومخاطر الرجوع في الوعد من طرف الزبون أو عدم سداد الأقساط، لذلك تسعى البنوك الإسلامية لإدارة مخاطرها بشكل جيد بحثا عن العائد المرتفع، من خلال فرض هامش الجدية، غرامات المماطلة. بالإضافة إلى عمليات الرهن العقاري والتأمين التكافلي وقد اعتمدنا في إنجاز هذه الدراسة على المنهج الوصفي مستعملين التحليل، بالإضافة إلى المقابلة كأدوات لجمع المعلومات عند دراسة حالة إدارة مخاطر نشاط التمويل العقاري ببنك البركة الجزائري وكالة الوادي وتوصلت الدراسة إلى أن هناك مجموعة من صيغ التمويل الإسلامي المناسبة للمجال العقاري والصالحة لتطبيقها في بنك البركة الجزائري وكالة الوادي لكنه اعتمد على صيغتين وهما: الإجارة المنتهية بالتمليك والاستصناع وذلك بسبب انخفاض مستوى المخاطر فيهما. أما عملية إدارة مخاطره فتتم على مستوى جميع مصالح البنك وليس لها جهة خاصة مكلفة بها، وذلك عن طريق تطبيق شروط التمويل العقاري الصادرة عن بنك البركة الجزائري الأم. "This thesis centers on assessing the effectiveness of procedures and methods used in managing the risks associated with Islamic home financing contracts. It explores the various Sharia-compliant financing instruments tailored for the real estate sector. Islamic banks are exposed to a range of risks that may jeopardize their sustainability, including two main categories: general risks shared with conventional banks—such as credit, liquidity, and market risks—and specific risks inherent to Islamic financing contracts. The latter include Shariah compliance risks, the increased costs related to the maintenance and preservation of financed properties, and risks stemming from client default or withdrawal from binding promises. To mitigate these risks and ensure sustainable profitability, Islamic banks implement several risk management strategies, such as applying seriousness margins, imposing penalties for late payments, and utilizing collateral-based arrangements and Takaful (Islamic insurance).This study adopts a descriptive and analytical approach, relying also on field interviews to examine risk management practices in real estate financing at Al Baraka Bank – El Oued Branch. The findings indicate that while several Islamic financing modes are theoretically applicable to the real estate sector, the bank primarily adopts two: Ijara Muntahia Bittamleek (lease-to-own) and Istisna’a (construction/manufacturing contract), due to their relatively lower risk levels. Moreover, risk management at the branch is conducted across all departments rather than through a dedicated unit, and it adheres to the real estate financing guidelines issued by the central Al Baraka Bank in Algeria.
ماستر
Keywords: بنوك إسلامية; صيغ التمويل الإسلامي; إدارة مخاطر; تمويل عقاري; Islamic banks; Islamic financing formulas; risk management; real estate financing.